2017
DOI: 10.1103/physrevlett.119.038001
|View full text |Cite
|
Sign up to set email alerts
|

Self-Organized Resonance during Search of a Diverse Chemical Space

Abstract: Recent studies of active matter have stimulated interest in the driven self-assembly of complex structures. Phenomenological modeling of particular examples has yielded insight, but general thermodynamic principles unifying the rich diversity of behaviors observed have been elusive. Here, we study the stochastic search of a toy chemical space by a collection of reacting Brownian particles subject to periodic forcing. We observe the emergence of an adaptive resonance in the system matched to the drive frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 19 publications
4
46
0
Order By: Relevance
“…These results suggest that CWs obey the SLS model across the scales, and raise the possibility that a biological feedback ensuring specific multiscale viscoelastic behavior is necessary for plants to maintain wild-type growth and morphology. Our results can also be put in the context of recent work that shows that cellular Gibbs energy dissipation also correlates linearly with growth in walled organisms (yeast) until it reaches saturation [46]; these results point towards a general behavior emerging from of the physics out of equilibrium that underpins growth of walled cells/organisms, where the use of metabolic energy is mirrored by that of the mechanical energy.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…These results suggest that CWs obey the SLS model across the scales, and raise the possibility that a biological feedback ensuring specific multiscale viscoelastic behavior is necessary for plants to maintain wild-type growth and morphology. Our results can also be put in the context of recent work that shows that cellular Gibbs energy dissipation also correlates linearly with growth in walled organisms (yeast) until it reaches saturation [46]; these results point towards a general behavior emerging from of the physics out of equilibrium that underpins growth of walled cells/organisms, where the use of metabolic energy is mirrored by that of the mechanical energy.…”
Section: Discussionsupporting
confidence: 70%
“…In other words, time relaxation processes present a memory effect [45], and hence it can be expected that nm-scale properties at high frequencies can present a correlation with macroscopic properties such as growth; indeed our results experimentally demonstrate that correlation. The resonance modes of a polymer are related to its Rg and are dominated by the lowest mode [46]. For a typical cell of 20 µm width, it can be expected that Rg ∼ 10 µm; therefore the lowest mode for a polymer made only from glucose would be fcell ≈ 60 kHz, which matches the magnitude of the frequencies used in our study.…”
Section: Physics Of Complex Hierarchical Polymeric Structures and Grsupporting
confidence: 79%
See 1 more Smart Citation
“…Some recent promising work in this direction can be found in FEP-AI, in terms of synchronous dynamics emerging through collaborative inference among interacting oscillators (Palacios et al, 2019). This kind of coordination in FEP-AI is often described in terms of the near ubiquitous phenomenon whereby systems minimize free energy through generalized synchrony (Strogatz, 2012;Kachman et al, 2017), as first demonstrated by Huygens with respect to pendulum clocks (Willms et al;Oliveira and Melo, 2015). Here, I will provide an informal sketch of how SOHM-formation might proceed and the potential functional consequences that may result from these processes:…”
Section: Cognitive Cycles and Fluctuating Substrates Of Consciousness?mentioning
confidence: 99%
“…From an FEP-AI perspective, this coupling relationship is one of mutual modeling and collaborative inference (Friston and Frith, 2015;Friston, 2017;Kirchhoff et al, 2018;Palacios et al, 2019). This generalized synchrony (Strogatz, 2012) has also been characterized in thermodynamic terms (Kachman et al, 2017;Friston, 2019), where systems spontaneously self-organize into resonant modes with the environments with which they couplei.e., absorb work and minimize free energy according to Hamilton's principle of least actionwhere coordinated dynamics have been observed to contain mutually predictive information (Friston, 2013). Notably, coupled attractors have recently been found to adjust their dynamics beginning at sparsely frequented areas of phase space (Lahav et al, 2018).…”
Section: Generalized Hpp and Universal Bayesianism/darwinismmentioning
confidence: 99%